A study of comparing single dose granisetron with combination of granisetron with dexamethasone in preventing postoperative nausea vomiting in laparoscopic cholecystectomies - Wadaskar, Dhawal R.; Magar, Jyoti S.; Tendolkar, Bharati A. (International Journal of Research in Medical Sciences, 2017)
Background: Postoperative nausea and vomiting (PONV) remains a vexing problem despite of advances in anaesthesia care. PONV is distressing adverse effect after anaesthesia and surgery, resulting in significant morbidity due to acute discomfort associated with emetic symptoms and longer stays in the recovery room or unexpected hospital admission in ambulatory settings. Methods: A prospective, randomized, double blind comparative study was conducted to compare the efficacy and adverse effects of injection granisetron 40µg/kg as a single dose and injection granisetron in two different doses (20µg/kg and 40µg/kg) in combination with dexamethasone 160µg/kg for prevention of postoperative nausea and vomiting in patients undergoing general anaesthesia for elective laparoscopic cholecystectomy. Results: Nausea and vomiting were observed postoperatively at 0, 1, 2, 4, 8, and 24 consecutive hours after patient responded to verbal commands. Intensity of nausea graded verbally with an eleven point score (0-10) with those patients who scored their nausea as zero were termed nausea free, and 10 being most severe. Nausea scores when patient complains of nausea & if patient demand rescue antiemetic for nausea was noted down along with adverse effects if any. The data was analysed by ANOVA followed by unpaired‘t’ test, Chi-square/Fischer exact test or Kruskal Wallis Test. Conclusions: Granisetron as a single agent in dose 40µg/kg is effective as prophylactic antiemetic in preventing PONV in laparoscopic cholecystectomy whereas addition of dexamethasone 160µg/kg to granisetron significantly increases antiemetic efficacy of the granisetron in both the doses i.e. 20µg/kg and 40µg/kg without increasing any side effect. Granisetron 40µg//kg+injection dexamethasone 160µg/kg is best for antiemetic prophylaxis in highly emetogenic surgeries like laparoscopic cholecystectomy. Granisetron 20µg/kg + injection dexamethasone can be cost effective alternative for routine antiemetic prophylaxis compared to granisetron 40µg//kg and granisetron 40µg//kg+ injection dexamethasone for all patients undergoing laparoscopic cholecystectomy.